Clinical, Biochemical, and Physiological Predictors of Postoperative Pulmonary Complications After Major Thoracic and Abdominal Surgery: A Cross-Sectional Clinical Study - Rifat Latif, Khalil Ahmed Shaikh, Ahmad Naeem Kiani, Muhammad Ilyas, Muhammad Kashif Rafiq, Hafiz Usman Khalid Ranjha (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Pulmonary complications are a source of morbidity following major thoracic and abdominal surgery. Objectives: To identify clinical, biochemical and physiological risk factors for postoperative pulmonary complications following major thoracic and abdominal surgery. Methods: The study was a cross-sectional clinical study carried out in the Department of Anaesthesia, Ayub Teaching Hospital, Abbottabad, Pakistan, and the Department of General Surgery, Mohtarma Benazir Bhutto Shaheed Medical College, Mirpur, Pakistan, from June 2022 to June 2023. One hundred twenty (120) adult patients that were undergoing major thoracic or abdominal surgery under general anesthesia were included. Clinical features, biochemical data and physiological data, and postoperative pulmonary complications were documented. SPSS version 26 software was used for data analysis. Results: Postoperative pulmonary complications occurred in 34 patients (28.3%). Complications patients were older, higher BMI, smoking history, COPD, diabetes mellitus, emergency surgery, longer operation time, more blood loss and more ICU admission. Biochemical parameters which were found to be raised were leucocyte count, NLR, CRP, serum lactate, creatinine, random blood sugar, low hemoglobin and hypoalbuminemia. Physiological predictors were included higher respiratory rate, lower SpO2, lower PaO2/FiO2 ratio, lower FEV1, and lower FVC. Multivariable analysis identified PaO₂/FiO₂ ratio <300, serum albumin <3.5 g/dL, ASA III–IV, COPD, FEV₁ <70%, length of surgery, smoking, raised CRP and Age >60 years as independent predictors. Conclusion: Post op pulmonary complications were prevalent following major thoracic and abdominal surgery. Perioperative risk stratification might be better achieved with a combination of clinical, biochemical, and physiological assessment. Keywords: Postoperative pulmonary complications; thoracic surgery; abdominal surgery; PaO₂/FiO₂ ratio; hypoalbuminemia; perioperative risk